Brg1 is required to maintain colorectal cancer stem cells. Issue 3 (20th August 2021) - Yoshikawa, Takaaki; Fukuda, Akihisa; Omatsu, Mayuki; Namikawa, Mio; Sono, Makoto; Fukunaga, Yuichi; Masuda, Tomonori; Araki, Osamu; Nagao, Munemasa; Ogawa, Satoshi; Masuo, Kenji; Goto, Norihiro; et al.
Abstract: Tumor cells capable of self‐renewal and continuous production of progeny cells are called tumor stem cells (TSCs) and are considered to be potential therapeutic targets. However, the mechanisms underlying the survival and function of TSCs are not fully understood. We previously reported that chromatin remodeling regulator Brg1 is essential for intestinal stem cells in mice and Dclk1 is an intestinal TSC marker. In this study, we investigated the role of Brg1 in Dclk1 + intestinal tumor cells for the maintenance of intestinal tumors in mice. Specific ablation of Brg1 in Dclk1 + intestinal tumor cells reduced intestinal tumors in Apc Min mice, and continuous ablation of Brg1 maintained the reduction of intestinal tumors. Lineage tracing in the context of Brg1 ablation in Dclk1 + intestinal tumor cells revealed that Brg1 ‐null Dclk1 + intestinal tumor cells did not give rise to their descendent tumor cells, indicating that Brg1 is essential for the self‐renewal of Dclk1 + intestinal tumor cells. Five days after Brg1 ablation, we observed increased apoptosis in Dclk1 + tumor cells. Furthermore, Brg1 was crucial for the stemness of intestinal tumor cells in a spheroid culture system. BRG1 knockdown also impaired cell proliferation and increased apoptosis in human colorectal cancer (CRC) cells. Microarray analysis revealed that apoptosis‐related genes were upregulated and stem cell‐related genes were downregulated in human CRC cells by BRG1 suppression. Consistently, high BRG1 expression correlated with poor disease‐specific survival in human CRC patients. These data indicate that Brg1 plays a crucial role in intestinal TSCs in mice by inhibiting apoptosis and is critical for cell survival and stem cell features in human CRC cells. Thus, BRG1 represents a new therapeutic target for human CRC. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.